State of stress of a hull structure rammed by the bow of another vessel - Mădălina Prodan (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding, 2016)
The study of structural strength of the hull structure is essential to determine the safety and integrity of the ship, in case of collision. The objective of this work is to study the impact loading of a ship bow on a strengthened plane structure, using FEA software ABAQUS.